Parasite rearing and infection temperatures jointly influence disease transmission and shape seasonality of epidemics. Issue 9 (31st July 2018) - Shocket, Marta S.; Vergara, Daniela; Sickbert, Andrew J.; Walsman, Jason M.; Strauss, Alexander T.; Hite, Jessica L.; Duffy, Meghan A.; Cáceres, Carla E.; Hall, Spencer R.
Abstract: Seasonal epidemics erupt commonly in nature and are driven by numerous mechanisms. Here, we suggest a new mechanism that could determine the size and timing of seasonal epidemics: rearing environment changes the performance of parasites. This mechanism arises when the environmental conditions in which a parasite is produced impact its performance—independently from the current environment. To illustrate the potential for "rearing effects", we show how temperature influences infection risk (transmission rate) in a Daphnia ‐fungus disease system through both parasite rearing temperature and infection temperature. During autumnal epidemics, zooplankton hosts contact (eat) fungal parasites (spores) reared in a gradually cooling environment. To delineate the effect of rearing temperature from temperature at exposure and infection, we used lab experiments to parameterize a mechanistic model of transmission rate. We also evaluated the rearing effect using spores collected from epidemics in cooling lakes. We found that fungal spores were more infectious when reared at warmer temperatures (in the lab and in two of three lakes). Additionally, the exposure (foraging) rate of hosts increased with warmer infection temperatures. Thus, both mechanisms cause transmission rate to drop as temperature decreases over the autumnal epidemic season (from summer to winter). Simulations show how these temperature‐driven changes in transmission rate can induce waning of epidemics as lakes cool. Furthermore, via thermally dependent transmission, variation in environmental cooling patterns can alter the size and shape of epidemics. Thus, the thermal environment drives seasonal epidemics through effects on hosts (exposure rate) and the infectivity of parasites (a rearing effect). Presently, the generality of parasite rearing effects remains unknown. Our results suggest that they may provide an important but underappreciated mechanism linking temperature to the seasonality of epidemics.